2007
DOI: 10.1016/j.addbeh.2007.04.026
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cigarette smoking on script-driven imagery in smokers with and without posttraumatic stress disorder

Abstract: The study investigated the effects of smoking a nicotinized or denicotinized cigarette on craving, affect and posttraumatic stress disorder (PTSD) symptoms while recalling neutral, stressful and traumatic events in smokers with and without PTSD. Smokers completed laboratory sessions during which they were presented with audiotapes of personalized scripts followed by smoking a cigarette. The effect of the script and cigarette conditions on dependent variables was evaluated. There was a main effect of script typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 81 publications
6
60
0
Order By: Relevance
“…Dichotomizing current smoking status limited our ability to investigate certain lines of inquiry; future studies of smoking and PTSD in orofacial pain populations would do well to use a valid measure of smoking or a nicotine dependence scale as a continuous variable. Our discussion of possible links among motivation to regulate affect, outcome expectancies, and the moderating impact of smoking on the relationship between PTSD symptom severity and affective distress appears to be consistent with our data and with the characteristics of smoking in PTSD as noted in previous studies (Beckham et al 2004;Beckham et al 2005;Beckham et al 2007;Cook et al 2007;Feldner et al 2007;Marshall et al 2008). However, no direct measures of smoking motives or expectancies were included in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Dichotomizing current smoking status limited our ability to investigate certain lines of inquiry; future studies of smoking and PTSD in orofacial pain populations would do well to use a valid measure of smoking or a nicotine dependence scale as a continuous variable. Our discussion of possible links among motivation to regulate affect, outcome expectancies, and the moderating impact of smoking on the relationship between PTSD symptom severity and affective distress appears to be consistent with our data and with the characteristics of smoking in PTSD as noted in previous studies (Beckham et al 2004;Beckham et al 2005;Beckham et al 2007;Cook et al 2007;Feldner et al 2007;Marshall et al 2008). However, no direct measures of smoking motives or expectancies were included in this study.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with past work (Feldner et al, 2008). These results utilize a trauma-exposed sample with varying levels of posttraumatic stress (mostly without PTSD) to extend previous work, which demonstrated that smokers with PTSD compared with those without PTSD report more anxiety and smoking craving following both trauma-related and general stress scripts (Beckham et al, 2007). Furthermore, the observed difference with respect to the role of posttraumatic stress symptom severity and anxious arousal at Minutes 1-2, and in contrast to Minutes 3-4 of the challenge, may be due to an increasing perceived intensity of the challenge over time as well as limited statistical power as a function of the sample size.…”
Section: Discussionsupporting
confidence: 89%
“…The association between PTSD symptoms and ad lib smoking in PTSD smokers (Beckham, Feldman, Vrana et al, in press) is consistent with previous laboratory findings in which exposure to trauma cues increased urges to smoke (Beckham, Dennis, McClernon et al, 2005;Beckham et al, 1996), as well as with a study showing that people suffer from smoking withdrawal symptoms consistent with their psychiatric symptomatology (Pomerleau et al, 2000). These findings suggest that at least in some psychiatric populations, smoking may represent a form of self-medication of their psychiatric symptoms (Kassel et al, 2003).…”
Section: Summary and Recommendations For Smoking Cessation Interventisupporting
confidence: 86%